2022
DOI: 10.4178/epih.e2022028
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies in the community based on participants in the 2020 Korea National Health and Nutrition Examination Survey

Abstract: Objectives:The Korea National Health and Nutrition Examination Survey (KNHANES) is a nationwide cross-sectional surveillance system that assesses the health and nutritional status of the Korean population. To evaluate the occurrence of SARS-CoV-2 infection in the community, we investigated the presence of antibodies against SARS-CoV-2 using the sera of KNHANES participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The social capital sub-factor that influenced self-rated health was social network—developmentally disabled people with better-developed networks displayed higher self-rated health levels. The findings support prior studies [ 24 , 30 , 31 , 32 , 33 , 34 ] that demonstrated the impact of social networks on health. Trust, however, did not have a significant direct impact on health in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The social capital sub-factor that influenced self-rated health was social network—developmentally disabled people with better-developed networks displayed higher self-rated health levels. The findings support prior studies [ 24 , 30 , 31 , 32 , 33 , 34 ] that demonstrated the impact of social networks on health. Trust, however, did not have a significant direct impact on health in this study.…”
Section: Discussionsupporting
confidence: 90%
“…However, referring to a report from the residual serum samples of participants recruited between 24 April and 12 December 2020 from Korea National Health and Nutrition Examination Survey (KNHANES) including 19.0% of 70 or older, the seropositivity rate was just 0.09% (5/5284). It means there were few hidden undiagnosed infections (asymptomatic patients) in the community in 2020, due to the thorough 3T strategy (testing, tracing, treatment) [ 29 ]. Therefore, we guess that the participants in this study, who were community-dwelling older adults, had much lower rate of having caught COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Informal care remains the most common source of home care in the United States, with the use of informal home care by older adults with disabilities increasing from 2004 to 2016; nearly three-quarters of older adults with disabilities received informal home care in 2016. In Korea, family members account for the highest percentage of main caregivers, but the proportion of formal caregivers is increasing continuously ( 3 ).…”
Section: Introductionmentioning
confidence: 99%